Digital Transformation and Operational Resilience in Indonesian SMEs - Rodiansjah, Agis Ahmad; Hidayat, Agus Rohmat; Alifah, Nur; Hardiyanto, Feri (GEMA EKONOMI, 2026)
Background: This study examines the role of digital transformation in enhancing operational resilience among Indonesian SMEs. Amid rising uncertainty, technological disruption, and post-pandemic recovery, SMEs must sustain operations, protect resources, and respond rapidly to change. With limited buffers, SMEs require adaptive strategies, making digital transformation a key pathway to maintain performance and strengthen competitiveness. Objective: This study aims to determine the effect of digital transformation on operational resilience and to clarify the underlying mechanisms. It specifically evaluates the mediating roles of organizational agility and dynamic capabilities in strengthening resilience outcomes among Indonesian SMEs. Method: This research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 320 SME owners across Indonesia. The analysis examines the relationships between digital transformation, operational resilience, and related organizational constructs. Result: The findings indicate that digital transformation significantly influences operational resilience. This effect is mediated by organizational agility and dynamic capabilities. Digital adoption enhances responsiveness, flexibility, and recovery speed. SMEs leveraging digital platforms, data-driven decision-making, and agile processes demonstrate stronger resilience performance. Conclusion: Digital transformation enables Indonesian SMEs to adapt and recover effectively under adverse conditions. The study proposes an integrated framework linking digital transformation, agility, dynamic capabilities, and resilience, contributing to strategic management literature while offering practical insights for SMEs and policymakers.